Comparative Evaluation of Large Language Models for Translating Radiology Reports into Hindi - Amit Gupta; Ashish Rastogi; Hema Malhotra; Krithika Rangarajan (Indian Journal of Radiology and Imaging)
Objective The aim of this study was to compare the performance of four publicly available large language models (LLMs)—GPT-4o, GPT-4, Gemini, and Claude Opus—in translating radiology reports into simple Hindi.